PREVALENCE OF NEWCASTLE DISEASE VIRUS ANTIBODIES IN GALLUS GALLUS IN LIMA. CASE CONTROL STUDY - Ferrer M., Rocky (2008)
The present research work evaluated the results of 390 serum samples collected to birds reared in commercial farms (broilers, egg-laying hens, and breeders) and 343 serum samples collected to birds reared in non-technical farms (backyard and fighting birds) that were analyzed by the hemoagglutination inhibition (HI) test for the Newcastle disease (ND). Samples were collected by the SENASA (national authority for animal health) as part of a national serological survey in the second semester of year 2001. An interpretation table for the results of the HI test was designed by a team of experts taking into consideration the number and type of vaccines against ND used. The prevalence rate of birds with antibody titers compatible to a Newcastle virus challenge was 1.8 ± 1.3% in birds from commercial farms and 9.9 ± 3.2% in birds from non-technical farms. The logistic regression analysis showed that birds from non-technical farms represent a risk factor (p<0.0001) in obtaining antibody titers compatible to a Newcastle virus challenge (Odds Ratio was 6.02 with confidence interval of 2.6-13.8) as compared to birds from commercial farms. The results showed that the ND virus is endemic in the area of Lima, especially in birds of non-technical farms.